AUTOMATION SYSTEM OF A 30 HP BOILER TO IMPROVE ENERGY EFFICIENCY USING THERMODYNAMIC VARIABLES - Ubaldo Apaza, - (2014)
The implementation of an automatic control system in the fire-tube boiler of the Unit Operations Laboratory of the FIQT-UNI was performed to improve the utilization of the steam generated by it. The first point implemented had been an automatic purge using a ladder programming language established in a relay. This system allows the automatic purge by using a pneumatic valve; the second point was the implementation of a monitoring system, supervision and data logging of the temperature flue gas and as a last point, the implementation of a portable flue gas analyzer and the total steam duct insulation in order to minimize energy losses.The best results of this research could be applied ,through the same process, on an industrial level in industries which use boilers as their heart for their various processes in order to obtain improvements in their processes and in their operation costs.